Comparative antiplatelet activity of COX1 NSAIDS versus aspirin, encompassing regimen simplification and gastroprotection: a call for a controlled study - B. Rothschild (PAGEPress Publications, 2004)
The cardioprotective/platelet inhibitory role of non-steroidal antiinflammatory drugs (NSAIDs) has been controversial, perhaps in contrast to the accepted prophylactic role of aspirin (114). That cardioprotective effect is attributed to the platelet aggregation inhibitory effects of aspirin and COX 1 active NSAIDS (10, 11, 13) and can be studied without requirement for massive numbers of patients. Such cardioprotection, however, has its own risks. Significant gastrointestinal toxicity is still present with the 75-81 mg aspirin dose and appears no less than that found with the higher doses once routinely utilized in treatment of arthritis (2, 8, 9). One study even reported that 4% of patients receiving aspirin had moderate to severe bleeding (14). The challenge with aspirin is that even with a 75 mg dose, the frequency of severe gastrointestinal hemorrhage is double that of placebo (2, 8, 9) and not different from that observed with COX 1 NSAIDs, in the abse